An assessment of speech, language, and literacy of children of young mothers attending supported playgroup. Issue 9 (4th July 2022) - Krahe, Michelle; O'Leary, Kate; Reilly, Sheena; Ellis, Kate; Walsh, Karyn
ABSTRACT: Children growing up in disadvantage are more vulnerable to speech, language, and literacy difficulties, which are important in the acquisition of many different life skills. Despite supported playgroups engaging directly with families living in disadvantage, very few speech and language studies have been delivered within this setting. This study aimed to identify needs related to speech, language, and literacy of children of young mothers who were attending a supported playgroup in Brisbane, Australia. This was a cross-sectional study with 11 mother–child dyads. Child assessments were delivered by a speech pathologist and compared with normative data. Results indicate that children's speech and language skills were age-appropriate, despite presenting with some speech sound errors. Children aged 4–5 years had difficulty with some literacy tasks. These findings suggest that future research or language interventions for the supported playgroup setting should provide language-learning opportunities that address speech sound production and early literacy skills.